2015
DOI: 10.1007/s11934-015-0530-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Multi-parametric Prostate MRI in Clinical Practice

Abstract: While initial implementations of prostate MRI suffered from suboptimal performance in tumor detection, technological advances over the past decade have allowed modern multi-parametric prostate MRI (mpMRI) to achieve high diagnostic accuracy for detection, localization, and staging and thereby impact patient management. A particular emerging application of mpMRI is in the pre-biopsy setting to allow for MRI-targeted biopsy, for instance, through real-time MRI/ultrasound fusion, which may help reduce the over-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The concept was mainly used for prostate cancer evaluation and staging due to the lack of specificity of conventional methods (prostate-specific antigens, digital rectal examination, and transrectal ultrasound biopsy). Prostate MRI provides an excellent assessment of the standard anatomical sequence, and the additional information from the contrast medium offers high accuracy for tumor detection localization and staging, thus influencing related management [18].…”
Section: Discussionmentioning
confidence: 99%
“…The concept was mainly used for prostate cancer evaluation and staging due to the lack of specificity of conventional methods (prostate-specific antigens, digital rectal examination, and transrectal ultrasound biopsy). Prostate MRI provides an excellent assessment of the standard anatomical sequence, and the additional information from the contrast medium offers high accuracy for tumor detection localization and staging, thus influencing related management [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the PI-RADS v2 also requires that many image features of DWI be used for image interpretation, such as dimension, boundary, shape, signal intensity, and homogeneity (Weinreb et al, 2016). However, each image feature of DWI for PCa diagnosis was weighted differently (Westphalen and Rosenkrantz, 2014) and interpretation was subjective, which resulted in diagnosis performance that was highly reader-dependent (Kierans et al, 2015;Muller et al, 2015;Schimmöller et al, 2013). Therefore, it is reasonable that the features of DWI be extracted and weighted in the CAD system.…”
Section: Discussionmentioning
confidence: 99%
“…MpMRI is based on complicated imaging principles and various signal characteristics. Despite its potential, the interpretation of results by radiologists, especially for less experienced ones, is difficult (Kierans et al, 2015). Although the PI-RADS has recommendations for image reading and reporting, the inter-reader agreement of mpMRI interpretations remains barely satisfactory (Muller et al, 2015;Schimmöller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The advances in imaging technology have led to improvements in early detection, whereby the detection of CSPCa has become more frequent for urologists 4,5 . Prostate magnetic resonance imaging (MRI) has been in use for nearly two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate magnetic resonance imaging (MRI) has been in use for nearly two decades. Initially, its utility was mainly for disease localization and staging after histopathologic diagnosis was reached 4 . At present, it is used not only for detecting suspicious foci but also for targeting the prostate biopsies 5 .…”
Section: Introductionmentioning
confidence: 99%